Differentiation strategy winning customers by being different - Holt, Kevin (Strategic planner) (Abingdon, Oxon ; New York, NY : Routledge, 2022)
This comprehensive and richly illustrated book explains how to create a differentiation strategy--a strategy for being different in a way that causes customers to prefer your products and services to those of your competitors. Filled with frameworks, tools, and templates, this book will enable you to create a compelling answer to your customers' most fundamental question: Why should I buy from you instead of your competitors? What makes you different? The first half of the book provides an in-depth analysis of the concepts and principles that underlie the practice of differentiation, including the meaning of competitive advantage, competitive strategy, and customer-perceived value. The second half of the book explains how to create a differentiation strategy by identifying the target of your strategy, using customer research and creative problem-solving to design a unique offering, devising a value proposition that emphasizes a key benefit and the reasons to believe you will deliver the benefit, and designing the activity system that will implement your differentiation strategy. Business leaders in companies large and small, business students, and leaders in government, higher education, and the non-profit sector will gain a deep understanding of all that goes into creating a successful, difficult-to-copy differentiation strategy.
OCLC-licensed vendor bibliographic record.
Keywords: Strategic planning; Business planning; BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / Development / Business Development; BUSINESS & ECONOMICS / Marketing / General